Hysteresis compensation control of a dielectric elastomer vibration isolator - Meng, Lili; Bao, Wenjie; Li, Fucai; Li, Hongguang (Journal of low frequency noise, vibration, and active control, 2021)
This paper describes the design and fabrication of a dielectric elastomer actuator vibration isolator and accompanying hysteresis compensation controller. The results of experiments to elucidate the hysteresis properties and the quality of the vibration isolation are also presented. The model used to characterize the hysteresis properties of the dielectric elastomer actuator is based on the controlled auto-regressive model and employs the recursive least squares method. A closed-loop proportional–integral–derivative controller was developed to compensate the hysteresis and was tuned via the back propagation neural network algorithm. The results demonstrate that the controller can compensate the hysteresis of the dielectric elastomer actuator, and the dielectric elastomer actuator can be used to isolate incoming vibration from the base. When tested using a narrow band vibration in a 5 Hz band, the isolation of the dielectric elastomer actuator vibration isolator was 45.60% across the frequency band.